2007
DOI: 10.1111/j.1528-1167.2007.01241.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Spectroscopy in Animal Models of Epilepsy

Abstract: Summary:The noninvasive localization of the epileptogenic zone continues to be a challenge in many patients that present as candidates for possible epilepsy surgery. Magnetic resonance imaging (MRI) techniques provide accurate anatomical definition, but despite their high resolution, these techniques fail to visualize the pathological neocortical and hippocampal changes in a sizable number of patients with focal pathologies. Further, visualized lesions on MRI may not all produce seizures. One of the keys to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…The abnormal Cho concentrations could reflect gliosis or, more probably, changes in the chemical and functional nature of cell membranes (Duncan, 1996; Savic et al., 2004; Kuzniecky, 2004; Hiremath & Najm, 2007). Accumulating molecular and electrophysiologic data suggest altered cholinergic function in some models of seizure generation (Friedman et al., 2007), and 1 H‐MRS findings of increased Cho have been observed in rats in which seizures were induced by epileptogenic treatment, probably reflecting an increase in acetylcholine and phospholipids (Jope & Gu, 1991; Kish et al., 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The abnormal Cho concentrations could reflect gliosis or, more probably, changes in the chemical and functional nature of cell membranes (Duncan, 1996; Savic et al., 2004; Kuzniecky, 2004; Hiremath & Najm, 2007). Accumulating molecular and electrophysiologic data suggest altered cholinergic function in some models of seizure generation (Friedman et al., 2007), and 1 H‐MRS findings of increased Cho have been observed in rats in which seizures were induced by epileptogenic treatment, probably reflecting an increase in acetylcholine and phospholipids (Jope & Gu, 1991; Kish et al., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging techniques have currently advanced the diagnosis, management, and understanding of the pathophysiology epilepsies. Although it has been traditionally held that there is no radiologic abnormality in patients with idiopathic epilepsies, sophisticated image processing suggest that subtle structural or metabolic abnormalities may contribute to their pathophysiology, apparently making seamless the transition between the poles of idiopathic and symptomatic epilepsy (Duncan, 1996; Kuzniecky, 2004; Hiremath & Najm, 2007). In this study, we showed 1 H‐MRS reliability for detecting brain changes in BAFME and suggest its role as a useful adjunctive tool supporting this diagnosis based on familial and electrophysiologic data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choline, betaine and TMAO levels were also decreased in the p32cKO mouse brain. Previous studies reported decreased choline levels in animal models and epilepsy patients 35 , 36 . 3-Hydroxybutyrate is a metabolite produced from the degradation of glyceride and fatty acids.…”
Section: Discussionmentioning
confidence: 89%
“…Numerous studies, both clinically24,25 and on animals,26 have reported decreases in NAA levels that are associated with either neuronal dysfunction or neuronal damage in epilepsy 27,28. Studies on children with newly diagnosed temporal lobe epilepsy have also shown a significantly decreased NAA/Cr level in the temporal lobe compared with normal controls 29.…”
Section: Discussionmentioning
confidence: 99%